Cover Image. (19th January 2020) - Chen, Chia‐Yuan; Kuo, Ting‐Yang; Huang, Chien‐Wu; Jian, Zih‐Hong; Hsiao, Po‐Tsung; Wang, Chin‐Li; Lin, Jian‐Ci; Chen, Chien‐Yu; Chen, Chao‐Hsuan; Tung, Yung‐Liang; Tsai, Ming‐Chi; Huang, Kuan‐Min; et al.
Abstract : The cover image is based on the Research Article Thermal and angular dependence of next‐generation photovoltaics under indoor lighting by Chia‐Yuan Chen et al., Mhttps://doi.org/10.1002/pip.3211 . Cover image & Mai‐Hao Chang and Chia‐Yuan Chen Images